2019
DOI: 10.1016/j.jacbts.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biological Strategy for Myocardial Protection by Intracoronary Delivery of Mitochondria: Safety and Efficacy

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 48 publications
(112 reference statements)
1
58
0
1
Order By: Relevance
“…Interestingly, animal studies have shown that treatment with empagliflozin protected the diabetic rat heart following AMI, as evidenced by less IRI-induced mitochondrial fission, attenuated oxidative stress and enhanced mitophagy, although the effect on MI size and cardiac function was not evaluated [85] . Intriguingly, experimental animal studies have shown that injection of viable mitochondria into the ischaemic heart following AMI, was cardioprotective as evidenced by increased myocardial ATP levels, upregulated proteomic pathways for mitochondrial function, and replaced damaged mitochondrial DNA [86] . In the clinically relevant pig model, it has been demonstrated that intracoronary injection of autologous mitochondria at the onset of myocardial reperfusion (after 30 min of coronary artery ligation) reduced MI size and preserved cardiac function [86] , demonstrating potential feasibility for clinical application in AMI patients undergoing myocardial reperfusion by primary PCI.…”
Section: Mitoprotective Strategies In Ami Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, animal studies have shown that treatment with empagliflozin protected the diabetic rat heart following AMI, as evidenced by less IRI-induced mitochondrial fission, attenuated oxidative stress and enhanced mitophagy, although the effect on MI size and cardiac function was not evaluated [85] . Intriguingly, experimental animal studies have shown that injection of viable mitochondria into the ischaemic heart following AMI, was cardioprotective as evidenced by increased myocardial ATP levels, upregulated proteomic pathways for mitochondrial function, and replaced damaged mitochondrial DNA [86] . In the clinically relevant pig model, it has been demonstrated that intracoronary injection of autologous mitochondria at the onset of myocardial reperfusion (after 30 min of coronary artery ligation) reduced MI size and preserved cardiac function [86] , demonstrating potential feasibility for clinical application in AMI patients undergoing myocardial reperfusion by primary PCI.…”
Section: Mitoprotective Strategies In Ami Patientsmentioning
confidence: 99%
“…Intriguingly, experimental animal studies have shown that injection of viable mitochondria into the ischaemic heart following AMI, was cardioprotective as evidenced by increased myocardial ATP levels, upregulated proteomic pathways for mitochondrial function, and replaced damaged mitochondrial DNA [86] . In the clinically relevant pig model, it has been demonstrated that intracoronary injection of autologous mitochondria at the onset of myocardial reperfusion (after 30 min of coronary artery ligation) reduced MI size and preserved cardiac function [86] , demonstrating potential feasibility for clinical application in AMI patients undergoing myocardial reperfusion by primary PCI. In this regard, a small feasibility pilot study of 5 paediatric patients (who had sustained significant acute myocardial ischaemic injury during cardiac surgery) reported that intramyocardial injection of autologous mitochondria (harvested from skeletal tissue) was safe and improved cardiac function assessed by echocardiography [87] .…”
Section: Mitoprotective Strategies In Ami Patientsmentioning
confidence: 99%
“…As a matter of fact, mitochondria transplantation has been successfully tested in several animal models for mitochondrial diseases. In particular, this therapeutic approach has been invariably shown to significantly reduce hypoxic/ischemic insult and restore tissue function following myocardial infarction [ 173 , 174 , 175 , 176 ], acute kidney injury [ 177 ], stroke [ 178 , 179 ], spinal cord injury [ 180 , 181 ], or optic nerve crush leading to glaucoma [ 182 ] by improving the bioenergetics and cell survival and by decreasing oxidative stress and mitochondrial DNA damages. Similarly, mitochondria transplantation has been reported to exert beneficial effects in animal models for either metabolic syndromes, including diabetic ischemic heart [ 183 ] and non-alcoholic fatty liver [ 184 ], or for neurological disorders, such as Parkinson’s disease [ 185 , 186 ] and schizophrenia [ 187 ].…”
Section: Current Therapeutic Approaches and Clinical Trials For Thmentioning
confidence: 99%
“…In this issue of JACC: Basic to Translational Science , Shin et al. (6) extend their prior research in autologous mitochondrial transplant to direct myocardial injection and demonstrate that autologous mitochondrial transplantation with intracoronary delivery can potentially preserve myocardial blood flow in a swine ischemia-reperfusion model. Shin et al.…”
mentioning
confidence: 99%
“…Shin et al. (6) describe 3 sets of experiments and demonstrate that: 1) intracoronary autologous mitochondria can be safely administered and are taken up by the myocardium without hemodynamic consequences; 2) compared with nonviable or other cell types, autologous mitochondria transplantation leads to an increase in coronary blood flow, likely via inwardly rectifying potassium channels; and 3) autologous mitochondrial transplantation leads to a reduction in infarct size and cardiac remodeling in an ischemia-reperfusion model. The findings are indeed intriguing, although the proposed mechanistic benefits still need to explain the physiologic outcome differences, as the observed number of mitochondria taken up seemed relatively sparse.…”
mentioning
confidence: 99%